Effect of frying conditions on the physico-chemical properties of rice bran oil and its blended oil - Mishra, Richa (Springer India, 2011)
The changes occurring in rice bran oil and its blend with sunflower oil during repeated frying cycles of dried and moist potato chips were monitored. The parameters assessed were: Colour, Refractive Index, SpecificGravity, Oryzanol Value, Free fatty acid, Iodine Value, Peroxide value, anisidine value, Saponification Value, trans fats and fatty acid composition. No significant changes (p≤0.05) were observed in the refractive index and specific gravity of rice bran oil, sunflower oil and their model blend. The colour of blended oil was lesser than RBO and the intensity of color increased after each frying cycle during the deep fat frying of moistened and dried potato chips. The oryzanol content and iodine value decreased with the frying cycles. The decrease in oryzanol value during the frying operation was more prominent in rice bran oil as compared to the blended oils. The increase in p-anisidine value was more in rice bran oil as compared to blended oil. No significant changes (P<0.05) in the myristic, palmitic and stearic acid composition was observed during the repeated deep fat frying cycles in both the rice bran oil and blended oils samples. The amount of unsaturated fatty acid decreased gradually during repeated deep fat frying cycles in both the oils. The trans fat increased with repeated deep fat frying cycles in both the rice bran and blended oils, when used to fry moistened and dried potato chips. Both the oil samples showed greater formation of trans fatty acids when the moistened potato chips were used during frying.